PENGARUH PEMBELAJARAN PAI BERBASIS PROYEK TERHADAP KARAKTER RELIGIUS SISWA DI KURIKULUM MERDEKA - Ikat Sutriani; Agus Pahrudin; Agus Jatmiko; Koderi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the influence of project-based Islamic Education (PAI) learning on students’ religious character within the Merdeka Curriculum at SD Islam Assalam. The research problem concerns the limited empirical evidence regarding the effectiveness of project-based learning in strengthening spiritual attitudes, religious practice, and moral behavior among elementary students. The purpose of this study is to analyze the contribution of project-based PAI activities to character development and to identify the dominant factors influencing religious growth. A quantitative method was employed using a pre-experimental design involving sixth-grade students, consisting of two classes: 6A (24 students) and 6B (25 students), with a total of 49 participants. Data were collected through questionnaires, observation sheets, and documentation, and were analyzed using descriptive statistics and paired t-tests. The findings indicate a significant improvement in students’ religious character after participating in project-based PAI learning, particularly in aspects of worship habits, honesty, responsibility, and respect toward others. Collaborative project activities, real-life religious tasks, and reflective assessment were identified as key components that support the internalization of Islamic values. The study concludes that project-based PAI learning is effective in enhancing religious character and supports the successful implementation of the Merdeka Curriculum. Moreover, it is recommended as an innovative pedagogical model for PAI teachers in elementary schools and madrasah to foster students’ religious character through meaningful and authentic learning experiences.